Photocrosslinked biobased phase change material for thermal energy storage - KAHRAMAN, MEMET VEZİR (WILEY-BLACKWELL, 2016)
A series of novel photocrosslinked biobased shape-stabilized phase change materials (PCMs) based on octadecanol, eicosanol and docosanol have been prepared by UV technique for the purpose of thermal energy storage applications. Epoxidized soybean oil was reacted with acrylic acid to form acrylated soybean oil (ASO). The structure and composition, cross-section morphology, thermal stability performances and phase change behaviors of ASO and UV-cured PCMs were examined by using Attenuated total reflection fourier transform infrared spectroscopy, thermogravimetric analysis system (TGA), scanning electron microscopy, and differential scanning calorimetry. The results indicate that the UV-cured biobased PCMs possess perfect phase change properties and a suitable working temperature range. The heating process phase change enthalpy is measured between 30 and 68 J/g, and the freezing process phase change enthalpy is found between 18 and 70 J/g. The decomposition of UV-cured PCMs started at 260 degrees C and reached a maximum of 430 degrees C. All the biobased UV-cured PCMs improved latent heat storage capacity in comparison with the pristine ASO sample. With the obtained results we conclude that, these materials promise a great potential in thermal energy storage applications. (C) 2016 Wiley Periodicals, Inc.
Keywords: biopolymers & renewable polymers; differential scanning calorimetry; photopolymerization; thermal properties; HEAT-STORAGE; COMPOSITES; CONDUCTIVITY; HEXAHYDRATE; COPOLYMER; SYSTEMS; ACID